Simvastatin Inhibits Activation of NADPH Oxidase/p38 MAPK Pathway and Enhances Expression of Antioxidant Protein in Parkinson Disease Models - Tong, Huichun; Zhang, Xiuping; Meng, Xingjun; Lu, Lingli; Mai, Dongmei; Qu, Shaogang (Frontiers in Molecular Neuroscience, 2018)
ABSTRACT Evidence suggests that oxidative stress is involved in the pathogenesis of Parkinson disease (PD). Simvastatin has been suggested to protect against oxidative stress in several diseases. However, the molecular mechanisms by which simvastatin protects against neuropathology and oxidative damage in PD are poorly elucidated. In this study, we aimed to investigate the potential neuroprotective effects of simvastatin owing to its anti-oxidative properties in 6-hydroxydopamine (6-OHDA)-treated SH-SY5Y cells and mice. The results of 2’, 7’-dichlorodihydrofluorescein diacetate fluorescence and CCK-8 assay demonstrated that simvastatin reduced intracellular reactive oxygen species levels and reversed apoptosis in 6-OHDA-treated SH-SY5Y cells. Mechanistic studies revealed that 6-OHDA-induced activation of NADPH oxidase/p38 MAPK pathway was inhibited and nuclear factor-κB nuclear transcription decreased in SH-SY5Y cells after simvastatin treatment. Enhanced expression levels of superoxide dismutase, heme oxygenase-1, peroxisome proliferator-activated receptor-γ coactivator-1α, and glutamate-cysteine ligase modifier subunit were observed after simvastatin treatment in 6-OHDA-treated SH-SY5Y cells. In vivo studies revealed that administration of simvastatin by gavage decreased limb-use asymmetry and apomorphine-induced rotations in 6-OHDA-lesioned mice. Simvastatin increased dopaminergic neurons and reduced protein tyrosine nitration and gliosis in the midbrain of PD mice. An inhibitory effect on activation of the NADPH oxidase/p38 MAPK was observed, and increased antioxidant protein expression in the midbrain were seen in the simvastatin plus 6-OHDA group compared with the 6-OHDA-lesioned group. Taken together, these results demonstrate that simvastatin might inhibit the activation of NADPH oxidase/p38 MAPK pathway, enhance antioxidant protein expression, and protect against oxidative stress, thereby providing a novel antioxidant mechanism that has therapeutic validity.